The phenomena of contagion of digitalization inside European Regions - Félix Hernández de Rojas; Pilar Rodríguez Pita; Jorge Emiliano Pérez Martínez (International Telecommunications Society (ITS), 2024)
Lately, we have seen a growing concern for competitiveness, strategic autonomy, and the rising of digital divide in the European Digital Single Market. To tackle these issues, in 2023 the EU1 set forth the Digital Decade program that "empowers businesses and people in a human-centred, sustainable and more prosperous digital future"2, with the aim of attracting investment and creating an innovative and digital ecosystem "made in Europe". However, Europe faces a set of barriers that arise from the cultural, linguistic, and societal differences that exist between the Member States and that do not exist in other largely populated countries in Asia or America. Throughout our research, we have clustered the 240 NUTS2 regions of the EU by their digitalisation, based on the Digital Economy and Society Index, and their competitiviness, based on the EU Regional Competitiviness Index, and their respective variables. we have made use of the Moran's I and Geary's C that allows us to determine the degree of clustering of EU regions and giving us a hint on which regions are more susceptible to "digital contagion", and which regions are most likely of be left behind because of lack of this phenomena. Our research identifies the above aspects and analyzes them within the heterogeneity of digitalization situations in the regions, identifying those where this "digital contagion" or "spatial spillover" works satisfactorily and where it does not, as well as considering whether national or EU policies are relevant to this end.
Keywords: 330; Digital Contagion; Spatial Autocorrelation; NUTS2; European Union; Competitivity